Assessment of Knowledge Regarding First Aid among the Undergraduate Students: A Cross-Sectional Study - Melvin Jacob; Hezil Reema Barboza (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: First aid knowledge is very valuable for every individual in the community. It enables theindividual to assist the injured person in an emergency situation until medical help arrives at the site.1Students are highly exposed to different kinds of physical injuries. Lack of knowledge regarding managingthese medical injuries was noted among the students.2 Careful management recommended for reducing thecomplication. This study was conducted to determine the knowledge of first aid and its associated factorsamong undergraduate students.3-5Materials and Methods: A descriptive cross-sectional study was conducted among 100 undergraduatestudents. Subjects were selected using purposive sampling techniques. The information was collected usinga demographic proforma and a self-administered questionnaire. The overall knowledge on first aid wasgraded as adequate, good and inadequate.Results: The overall knowledge score was 13.81 ± 4.41. The mean percentage of the overall level ofknowledge was 57.54% which indicate the majority had good knowledge on aspects of first aid. In thisstudy there was no significant association between knowledge score and selected demographic variables.Conclusion: The study showed the majority had good knowledge of first aid. But also identified some keyareas in which first aid knowledge was deficient in the management of shock, burns and fracture. Thus thereis a need for first aid training to be introduced in the undergraduate curriculum of different disciplines. Thestudy recommends the use of modern techniques such as simulation with computerized mannequins as ateaching-learning method in all the educational institutions.